Airborne spread of severe acute respiratory syndrome coronavirus 2 between rooms in a sealed, mechanically ventilated ward: Evidence from a hospital outbreak investigation - Yo Ishigaki; Naohisa Fujita; Tatsuo Kato; Toshiya Ochiai; Haruo Kuroboshi; Akemi Sakane; Norio Asai (PLoS ONE, 2026)
Airborne transmission of severe acute respiratory syndrome coronavirus 2 in enclosed, mechanically ventilated hospital wards remains poorly characterized. In February 2025, a coronavirus disease cluster involving 17 individuals occurred across multiple rooms in a sealed Japanese hospital ward. Several infected individuals had no documented close contact with the index patient, raising concerns about ventilation-related airflow-induced inter-room aerosol transmission. A multimodal environmental investigation was conducted via (1) CO 2 decay experiments to quantify air change rates (ACHs), (2) particulate matter (PM) 2.5 aerosol dispersion measurements using fog as a surrogate tracer, and (3) computational fluid dynamics (CFD) simulations to visualize airflow and scalar transport. Measurements were taken in the index room (Room A), corridor, and adjacent Rooms B–D under closed- and open-door conditions. Opening the patient room door significantly increased indoor ACHs (3.29/h → 4.01/h, p = 0.030) and allowed CO 2 tracer gas to escape into the corridor. In the PM 2.5 dispersion experiment, aerosols released in Room A were detected within the room, corridor, and neighboring rooms, with the highest out-of-room aerosol burden observed at the corridor sensor (area under the curve = 2.6 × 10 5 μg·s/m 3 ). PM 2.5 and PM 10 concentrations were strongly correlated (r = 0.9997), revealing intermediate-sized particles capable of longer-range transport. CFD simulations reproduced key qualitative features of the experiments, including tracer accumulation within curtain-enclosed compartments, delayed leakage through the doorway, and downstream transport toward the corridor. Inter-room aerosol transport can occur in sealed, mechanically ventilated wards without natural ventilation or structural openings between rooms. Opening doors improves in-room ventilation and promotes aerosol leakage, revealing a trade-off between the dilution and contamination of shared spaces. Architectural elements such as privacy curtains contribute to airflow stagnation and uneven aerosol removal. Effective infection control strategies must incorporate airflow pathway management and localized filtration to prevent unintended aerosol migration in mechanically ventilated healthcare settings.